Intrafraction Prostate Motion Management During Dose-Escalated Linac-Based Stereotactic Body Radiation Therapy - Panizza, Denis; Faccenda, Valeria; Lucchini, Raffaella; Daniotti, Martina Camilla; Trivellato, Sara; Caricato, Paolo; Pisoni, Valerio; De Ponti, Elena; Arcangeli, Stefano (Frontiers in Oncology, 2022)
Background Extreme hypofractionation requires tight planning margins, high dose gradients, and strict adherence to planning criteria in terms of patient positioning and organ motion mitigation. This study reports the first clinical experience worldwide using a novel electromagnetic (EM) tracking device for intrafraction prostate motion management during dose-escalated linac-based stereotactic body radiation therapy (SBRT). Methods Thirteen patients with organ-confined prostate cancer underwent dose-escalated SBRT using flattening filter-free (FFF) volumetric modulated arc therapy (VMAT). The EM tracking device consisted of an integrated Foley catheter with a transmitter. Patients were simulated and treated with a filled bladder and an empty rectum. Setup accuracy was achieved by ConeBeam-CT (CBCT) matching, and motion was tracked during all the procedure. Treatment was interrupted when the signals exceeded a 2 mm threshold in any of the three spatial directions and, unless the offset was transient, target position was re-defined by repeating CBCT. Moreover, the displacements that would have occurred without any intrafraction organ motion management (i.e. no interruptions and repositionings) were simulated. Results In 31 out of 56 monitored fractions (55%), no intervention was required to correct the target position. In 25 (45%) a correction was mandated, but only in 10 (18%), the beam delivery was interrupted. Total treatment time lasted on average 10.2 minutes, 6.7 minutes for setup, and 3.5 minutes for beam delivery. Without any intrafraction motion management, the overall mean treatment time and the mean delivery time would have been 6.9 minutes and 3.2 minutes, respectively. The prostate would have been found outside the tolerance in 8% of the total session time, in 4% of the time during the setup, and in 14% during the beam-on phase. Predominant motion pattern was posterior and its probability increased with time, with a mean motion ≤ 2 mm occurring within 10 minutes. Conclusions EM real-time tracking was successfully implemented for intrafraction motion management during dose-escalated prostate SBRT. Results showed that most of the observed displacements were < 2 mm in any direction; however, there were a non-insignificant number of fractions with motion exceeding the predefined threshold, which would have otherwise gone undetected without intrafraction motion management.